Network pharmacology mechanisms and experimental verification of Hedyotis Diffusae Herba-Scutellariae Barbatae Herba drug pair extract in the treatment of nasopharyngeal carcinoma - Tiantian Li; Haijun Chen; Jing Zhang; Jiaxin Liu; Rundong Tang; Liang Zhang; Tian Feng; Yanchun Xiao; Shiwen Liu; Xiangjun Chen (Frontiers in Oncology)
BackgroundNasopharyngeal carcinoma (NPC) represents the predominant head-neck malignancy in China. While the Hedyotis Diffusae Herba-Scutellariae Barbatae Herba (HDH-SBH) herb pair shows antitumor potential, its mechanism against NPC remains unclear.MethodsThis network pharmacology study integrated with experimental validation identified NPC-related targets through GEO database and disease databases (OMIM, GeneCards, TTD). Active components of HDH-SBH and their targets were retrieved from Traditional Chinese Medicine Systems Pharmacology Database (TCMSP). Common targets were analyzed via STRING, with functional enrichment using Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG). Core components were validated through molecular docking and in vitro experiments using HDH-SBH-treated 5-8F and CNE2 cells.ResultsWe identified 36 bioactive components and 155 shared targets, with quercetin, luteolin, wogonin, and β-sitosterol emerging as core components. KEGG analysis highlighted PI3K/AKT pathway inhibition (P<0.05). Molecular docking confirmed strong binding between core components and key targets (AKT1, TP53, BCL2). In vitro validation showed HDH-SBH significantly inhibited NPC cell proliferation/migration while inducing apoptosis through downregulating BCL2, upregulating TP53, and suppressing AKT1 phosphorylation.ConclusionsBased on the network pharmacology approach, we predicted the potential mechanism of HDH-SBH for the treatment of NPC, which provided a new idea for further research on its pharmacological mechanism.